2017
DOI: 10.3329/jbt.v11i1.34245
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Corporate Attributes on Magnitude of Disclosure by Private Commercial Banks in Bangladesh

Abstract: The study reports

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Almalki et al (2012) discover a negative relationship between QWL and nurse turnover intention. In Bangladesh, research on QWL has found a negative influence on turnover intention (Newaz et al, 2007) and a positive effect on employee retention (Rahman et al, 2017). An individual's QWL directly influences the quality of life value (Sari et al, 2019) and the organization's productivity (Pio & Tampi, 2018).…”
Section: Hypotheses Development 251 Qwl and Employee Outcomesmentioning
confidence: 99%
“…Almalki et al (2012) discover a negative relationship between QWL and nurse turnover intention. In Bangladesh, research on QWL has found a negative influence on turnover intention (Newaz et al, 2007) and a positive effect on employee retention (Rahman et al, 2017). An individual's QWL directly influences the quality of life value (Sari et al, 2019) and the organization's productivity (Pio & Tampi, 2018).…”
Section: Hypotheses Development 251 Qwl and Employee Outcomesmentioning
confidence: 99%
“…On the other hand, the reporting and disclosure processes are pretty good. Rahman and Uddin (2016) examined how much information is disclosed and what factors affect it. Throughout the study, the average disclosure was determined to be 75.76 percent, and this percentage continued to rise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Larger organizations are likely to release more information than smaller ones. Bank size has been taken as a corporate attribute by examining various literature such as Hossain (2008), Rao and Desta (2016), Hasan and Hosain (2015), Rahman and Uddin (2016), Galani (2011), Hawashe (2015), Saha and Neogy (2022), Arif and Tuhin (2013), Barako (2007), Galani (2011), andNaveenan et al (2024).…”
Section: Corporate Attributes and Hypothesismentioning
confidence: 99%
“…However, age, profitability attributes, liquidity, and board composition have an insignificant impact on the level of disclosure. Rahman & Uddin (2016) have stated that log total assets, return on equity, and earnings per share significantly influence the disclosure level. On the other hand, log total no.…”
Section: Statement Of the Problemmentioning
confidence: 99%